SEWA KENDARAAN (RENTAL) DALAM PERSPEKTIF HUKUM ISLAM - Jailani, Jailani (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2021)
The objectives of this study are: 1) to determine the practice of renting a car at PT.Amanah Jaya and 2) to find out whether car rental at PT. Amanah Jaya is inaccordance with Islamic law. The results showed that the car rental agreement thatoccurred at Amanah Jaya Car Rental, Pademawu District, Pamekasan was carried outby both parties, namely, the car rental party as the provider of the service and theconsumer as the renter. The application of advances is not contrary to Islamic law onthe condition that there is no loss to either party and there is a willingness between thetwo parties. In the process of resolving delays and compensation for damages at PTAmanah Jaya, it was carried out by consensus. After that the disputing parties carryout the obligations that must be borne by each party in accordance with thepredetermined agreement.